QRIS ADOPTION DETERMINANTS: ANALYSIS OF THE ROLE OF EASE OF USE, TRUST, AND PROMOTION WITH USER SATISFACTION AS AN INTERVENING - Herlina; Suhardi; Astuti, Nelly; Hamdan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the determinants of QRIS adoption in Indonesia by integrating technological, psychological, and contextual perspectives. Using Structural Equation Modeling (SEM) on 320 user data, the study examined the influence of factors such as perceived ease of use (PEOU), user trust, promotion & education, and user satisfaction on QRIS adoption. The results show that user satisfaction and promotion-education have a significant effect on adoption, while ease of use only impacts satisfaction, not direct adoption. In contrast to classical theory, user trust is not significant in the Indonesian context, allegedly due to the dominance of financial incentive factors, government policies, and MSMEs' preference for practical benefits. These findings reinforce the relevance of Expectation-Confirmation Theory (ECT) and Diffusion of Innovation (DOI), while also highlighting the uniqueness of locality where targeted education and cashback programs are more effective than just system trust. The practical implications emphasize the need for an integrated strategy: economic benefit-based promotional campaigns, improved technical infrastructure to ensure the speed and security of transactions, and collaboration between regulators and service providers in expanding incentives for MSMEs. Further research is suggested to explore cultural factors (e.g., resistance to cashless transactions in rural areas) and qualitative approaches to understanding the perceptions of older generations. The study provides a holistic framework to accelerate the digital transformation of Indonesia's payments sector, prioritizing local context and real-world user experience.